An Integrative Literature Review and Future Directions of Decent Work (Global Journal of Management and Business Research, 2020)
The aim of decent work is to promote opportunities for women and men to obtain decent and productive work, in conditions of freedom, equity, security, and human dignity. Previous researches show that decent work has a significant impact on talent strategy on the national level, competitive advantage on organizational level and work demand meeting on the individual level. Thus, it draws much attention to home and abroad scholars. This paper reviews the previous research on decent work definition, dimensions, status quo, and related variables. Based on the research results and combined with the conservation of resource theory, this paper clarifies the definition and structure of decent work from the management perspective. From the perspective of resource gain spiral and resource loss spiral, this research proposes a theoretical framework of "perception of decent work-work attitude-work behavior". Accordingly, this study proposes suggestions for improving decent work by focusing on the definition of decent work on individual perspective, decent work scale development, and relationship among decent work perception, work attitude, and behavior in future research.
Keywords: decent work; proactive management; psychology of working theory